Water governance capacity: The art of dealing with a multiplicity of levels, sectors and domains - Edelenbos, Jurian; Teisman, Geert (International Journal of Water Governance, 2013)
This paper elaborates water issues as a problem of water governance capacity to face multiplicity of levels, sectors and domains. In order to do so, we will apply a complexity embracing theoretical approach, aiming to understand the interdependencies in the system that decline the effectiveness of one-sided top down interventions and urge for high quality interaction. Physical water systems as well as social systems dealing with water are considered to be complex and interconnected. The systems are compounded in the sense that there is no clear hierarchy and interconnected in the sense that the quality of the one can be heavily influenced by the other. The water systems touch upon other domains like agriculture, economic development, social development, ecology, health, etc. And along with these other physical system a variety of stakeholders, like industries, municipalities, farmers, recreational sector and environmental organizations comes along. All stakeholders do approach the problem and the possible solutions differently. In this paper we argue that complex nature of water governance processes call for the need for boundary spanning that leads to acting between domains, levels and sectors. Building up trustworthy relationships is crucial for gaining water governance capacity. We recommend a complexity embracing approach that focuses on boundary crossing capacities and capabilities.